CHEMICAL MANAGEMENT TIME OF SOIL COVER CROPS ON THE COMMON BEAN IN NO-TILLAGE SYSTEM - VALENTINI, Maria Helena Elias (Scientia Agraria, 2000)
It was carried out, at the ABC Foundation Experiment Station, Castro, PR, an experiment to study the effects of cover crops, and their chemical management time influence on the yield and components of dry beans. The experimental design was a randomized complete block utilizing splitplots with four replications The tested treatments were the combination of five cover çrops on the plots, and three chemical management times on the split-plots. The cover crops where white oats (Avena sativa), Black oats (Avena stflgosa), ryegrass (Lollítim maItíflorufll), forage turnip (Raphanus salivas), and Wheat (Trificam aestivum) and the chemical management times were 0, 15 and 30 days before seedling (DAS) the beans crop FT Bonito variety. Seedling the cover crops in three different limes guarantee the same amount of dry matter at the moment of species chemical management. An exception occurred with ryegrass that was submitted to an extra cut. Dry beans seeded on ryegrass cover crop showed the best initial and final plant populations. On white oats get the lowest initial plant population and on wheat the lowest final plant population. The chemical management limes did not showed any significant effect on the plant population. It was not verified, on the treatments, any significant difference on the average number of pods per plant, and seeds per pod, and on the yield. The mass average of 100 seeds was affected by the chemical management time and cover crop species. It was higher at 0 and 15 DAS for black oats and forage turnip, at 15 and DAS for white oats, at 0 and 30 DAS for wheat, and it was indifferent for ryegrass.